x/2+2y/3=-1 and x-y/3=3
Answers
Answered by
11
x/2+2y/3 = -1
x-y/3 = 3
=> x/2+2y/3 = -1
=> 3(x)+2(2y)/6 = -1 (making denominator equal)
=> 3x+4y = -6 (cross multiply). (equation 1)
x-y/3 = 3
=> 3(x)-y/3 = 3 (making denominator equal)
=> 3x-y/3 = 3
=> 3x-y = 9 (cross multiply). (equation 2)
subtract equation 2 from equation 1
=> 3x+4y-(3x-y) = -6-9
=> 3x-3x+4y+y = -15
=> 5y = -15
=> y = -15/5 => -3
if y = -3 then substitute this value of y in equation 2
=> 3x-y = 9
=> 3x-(-3) = 9
=> 3x+3 = 9
=> 3x = 6
=> x = 6/3 = 2
hope this helps
x-y/3 = 3
=> x/2+2y/3 = -1
=> 3(x)+2(2y)/6 = -1 (making denominator equal)
=> 3x+4y = -6 (cross multiply). (equation 1)
x-y/3 = 3
=> 3(x)-y/3 = 3 (making denominator equal)
=> 3x-y/3 = 3
=> 3x-y = 9 (cross multiply). (equation 2)
subtract equation 2 from equation 1
=> 3x+4y-(3x-y) = -6-9
=> 3x-3x+4y+y = -15
=> 5y = -15
=> y = -15/5 => -3
if y = -3 then substitute this value of y in equation 2
=> 3x-y = 9
=> 3x-(-3) = 9
=> 3x+3 = 9
=> 3x = 6
=> x = 6/3 = 2
hope this helps
Similar questions